Investigation of the geometry and electronic structure of endohedral complexes Pdn@C60, n=1,…,4, by quantum chemistry methods - G. E. Gal’pern; I. V. Stankevich; M. I. Skvortsova (Тонкие химические технологии)
The geometry, electronic structure and stability of endohedral complexes Pdn@C60, n=1,…,4, were investigated by a quantum chemistry method (DFT/PBE). The heat of formation ΔНf of a complex consisting of C60 and n Pd atoms was used as a measure of complex stability. In particular, it was is established that this reaction is exothermal for n=1-3 and endothermal for n=4.